Femmes artistes / Artistes femmes : Paris, de 1880 à nos jours. - Gonnard, Catherine; Lebovici, Elisabeth (Paris : Editions Hazans, 2007)
Aballéa, Martine ; Abbott, Berenice ; Ackein, Marcelle ; Akerman, Chantal ; Albert-Lazard, Lou ; Albin-Guillot, Laure ; Amer, Ghada ; Arcier, Raymonde ; Asse, Geneviève ; Bailly, Alice ; Ballet, Elisabeth ; Bass, Anna ; Bergmann, Anna Eva ; Bing, Ilse ; Blanchard, Maria ; Blocher, Sylvie ; Bossu, Sylvia ; Bourgeois, Louise ; Bournigault, Rebecca ; Breslau, Marie-Louise ; Brooks, Romaine ; Cahn, Marcelle ; Cahun, Claude ; Calle, Sophie ; Camax-Zoegger, Marie-Anne ; Carrington, Leonora ; Cassatt, Mary ; Charmy, Emilie ; Clairet, Alain ; Claisse, Geneviève ; Claudel, Camille ; Clavel, Olivia ; Cousturier, Lucie ; Croiset, Nicole ; cussol, Béatrice ; Delaunay, Sonia ; Dielman, Jeanne ; Exter, Alexandra ; Fini, Leonor ; Folâtre, Catherine ; Friedmann, Gloria ; Frydman, Monique ; Fuller, Loie ; Gastaldon, Vidya ; Gaussen-Saulmon, Jacqueline ; Gonzalez-Foerster, Dominique ; Halicka, Alice ; Henno, Laura ; Henri, Florence ; Hugo, Valentine ; Jaffé, Shirley ; Janicot, Françoise ; John, Gwen ; Jouve, Valérie ; Jugnet, Anne Marie ; Klonaris, Maria ; Krull, Germaine ; Laurencin, Marie ; de Lempicka, Tamara ; Lublin, Léa ; Maar, Dora ; Marquet, Andrée ; Messager, Annette ; Métadier, Champion ; Miller, Lee ; Miss Tic ; Mitchell, Joan ; Model, Lisette ; Modersohn-Becker, Paula ; Molnar, Vera ; Morisot, Berthe ; Moss, Marlow ; Mourad, Tania ; Münter, Gabriele ; Muter, Mela ; Negro, Marylène ; Nemours, Aurélie ; Nicola ; Oppenheim, Meret ; Orlan ; Orloff, Chana ; Pane, Gina ; Penrose, Valentine ; Poupelet, Jane ; Quinquaud, Anna ; Raymond, Marie ; Raynal, Jackie ; Reigl, Judit ; Richier, Germaine ; de Saint-Phalle, Niki ; Salomon, Charlotte ; Spero, Nancy ; Sturtevant, Elaine ; Taeuber-Arp, Sophie ; Thomadaki, Katerina ; Thurnauer, Agnès ; Toyen ; etc.
boek